Applicability of Voce equation for tensile flow and work hardening behaviour of P92 ferritic steel. (August 2015) - Sainath, G.; Choudhary, B.K.; Christopher, J.; Isaac Samuel, E.; Mathew, M.D.
Abstract: Detailed analysis of true stress (σ)-true plastic strain (ε) data indicated that tensile flow behaviour of P92 ferritic steel can be adequately described by Voce equation at strain rates ranging from 3.16 × 10 −5 to 1.26 × 10 −3 s −1 over a temperature range 300–923 K. The steel exhibited two-stage work hardening in the variations of instantaneous work hardening rate (θ = dσ/dε) with stress. At all the strain rates, the variations in σ-ε, θ-σ and work hardening parameters associated with Voce equation with temperature exhibited three distinct temperature regimes. At intermediate temperatures, the variations in σ-ε, θ-σ and work hardening parameters with temperature and strain rate exhibited anomalous behaviour due to the occurrence of dynamic strain ageing in the steel. The shift in θ-σ towards low stresses, and rapid decrease in flow stress and work hardening parameters with increasing temperature and decreasing strain rate suggested dominance of dynamic recovery at high temperatures. Highlights: Tensile flow and work hardening behaviour of P92 steel has been examined. Applicability of Voce equation to P92 steel is demonstrated. Three temperature regimes in flow and work hardening has been observed. Good match between predicted and the experimental tensile properties has been shown.